Evangelisasi di Indonesia: Teori dan Praktek - Sudhiarsa, Raymundus I Made (Perspektif, 2011)
As small minority and being dispersed community, the Christians in Indonesia are always challenged to present themselves amicably and attentively to people of other faiths. As integral part of Indonesian people they are of course responsible for the development of the society at large and the good of everyone, based on their calling to be light and salt of the world. They can accomplish this particular mission (missio ad extra) if their distinctive quality can be relied on. The article argues that the Church in Indonesia should at best work out the image of being salt or yeast rather than big tree. This theological image could be develop in line with the so-called 'theology of participation', since the Church has been elected to participate in missio Dei and to collaborate with people of other faiths in building up the nation-state of Indonesia to be a 'shared-world' of all.